Exploring COVID-19 vaccine uptake, confidence and hesitancy among people experiencing homelessness in Toronto, Canada: protocol for the Ku-gaa-gii pimitizi-win qualitative study. Issue 8 (17th August 2022) - Jenkinson, Jesse I R; Sniderman, Ruby; Gogosis, Evie; Liu, Michael; Nisenbaum, Rosane; Pedersen, Cheryl; Spandier, Olivia; Tibebu, Tadios; Dyer, Allison; Crichlow, Frank; Richard, Lucie; Orkin, Aaron; et al.
Abstract : Introduction: People experiencing homelessness are at high risk for COVID-19 and poor outcomes if infected. Vaccination offers protection against serious illness, and people experiencing homelessness have been prioritised in the vaccine roll-out in Toronto, Canada. Yet, current COVID-19 vaccination rates among people experiencing homelessness are lower than the general population. This study aims to characterise reasons for COVID-19 vaccine uptake and hesitancy among people experiencing homelessness, to identify strategies to overcome hesitancy and provide public health decision-makers with information to improve vaccine confidence and uptake in this priority population. Methods and analysis: The Ku-gaa-gii pimitizi-win qualitative study (formerly the COVENANT study) will recruit up to 40 participants in Toronto who are identified as experiencing homelessness at the time of recruitment. Semistructured interviews with participants will explore general experiences during the COVID-19 pandemic (eg, loss of housing, social connectedness), perceptions of the COVID-19 vaccine, factors shaping vaccine uptake and strategies for supporting enablers, addressing challenges and building vaccine confidence. Ethics and dissemination: Approval for this study was granted by Unity Health Toronto Research Ethics Board. Findings will be communicated to groups organising vaccination efforts in shelters, community groups and the City of Toronto to construct more targeted interventions that address reasons for vaccine hesitancy among people experiencing homelessness. Key outputs will include a community report, academic publications, presentations at conferences and a Town Hall that will bring together people with lived expertise of homelessness, shelter staff, leading scholars, community experts and public health partners.